El rincón de lectura en el desarrollo de la inteligencia lingüística de los niños y niñas de inicial ii paralelo “C” de la Unidad Educativa “Verbo Divino” del cantón Guaranda de la provincia Bolívar en el periodo 2024 - Lemache Alvarado, Andrea Alejandra (2024)
The present research focuses on the search for information for the proposal of a didactic guide of activities in the reading corner within the classroom to enhance the development of linguistic intelligence in children of initial II, being treated as a mixed methodological study and a wide range of information according to the variables with their respective work proposal. At present, learning corners have been key in the initial stages of children through student-teacher interaction. We have tried to make the respective review of authors, sources and reliable books on the subject, so we must take into account that everything flows in how the reading corner is shaped and also how the different teaching materials and playful activities can improve the communicative and linguistic skills of each child, increasing the ability of pronunciation and strengthening the habit of reading so that the child is able to give an opinion, through linguistic intelligence they can explore, create and imagine enriching stories and have a better expression of their vocabulary. In addition, it should be noted that the guide contains playful activities, creative pictographic, interactive songs and games through dialogue in conjunction with the teacher Lic. Veronica Bonilla, promoting the reading corner in the development of linguistic intelligence in children of Initial II being 16 girls and 16 boys of the parallel “C” of the Educational Unit “Verbo Divino